Review about Joaquín Oliver Pozo: The Inspection of Education of Andalusia. Origin, development and intervention in the centers - Gomera López, Francisco A. (Avances en Supervisión Educativa, 2015)
Autor: Joaquín Oliver Pozo Editorial: MAD Año de edición: 2015 Páginas: 466 Formato papel: Tapa blanda, 15x 23 cm. ISBN (en papel): 9788467673029